Living Well to Keep Your Pressure Down - Linda B. Bobroff (EDIS)
High blood pressure, or hypertension, can cause serious health problems. It makes your heart work harder and can damage your blood vessels even if you feel okay. Everyone should have their blood pressure checked regularly. If you have certain risk factors, you are more likely to have high blood pressure. This 6-page fact sheet is a major revision that discusses risk factors and ways to reduce risk.